RESEARCH ON IMPROVING THE FIRE RESISTANCE OF MODIFIED SULFUR-BASED CONCRETES - Akhmedov Islombek; S.Kholmirzayev; Umarov Isroil; F.Dadaxanov (Journal of new century innovations, 2023)
Annotation. The theoretical basis of sulfur concrete was studied in the article. A number of positive properties of sulfur concrete were studied, and the results of practical work on improving the fire resistance properties were studied.